Disclosure of joint ventures and associates in financial statement under IFRS - Petra Ašenbrenerová (European Financial and Accounting Journal, 2016)
This article deals with disclosure of associates and joint venture in financial statement. In May 2011 the IASB issued new standard IFRS 12 Disclosure of interest in other entities. This standard, compared with IAS 28 and IAS 31, requires to disclose more detail information about joint ventures and associates. The reason is elimination of proportionate consolidation for joint ventures and also users of financial statements requested improvements to the disclosure of a reporting entity's interests in other entities. The introductory section discusses the equity method and proportionate consolidation, which is followed by a chapter dealing with the disclosure of information relating to joint ventures and associates in the financial statements. The last part is devoted to an analysis of disclosed information relating to joint ventures associates in the financial statements of companies that are listed on the Prague Stock Exchange.
Keywords: M41; 650; Associates; Financial Statement; IFRS 12; Joint Ventures